Tìm x, biết: (3x-4)^2- (x-3)^2- 3(x-2)(2x-1)=0

Tìm x, biết: (3x-4)^2- (x-3)^2- 3(x-2)(2x-1)=0

2 bình luận về “Tìm x, biết: (3x-4)^2- (x-3)^2- 3(x-2)(2x-1)=0”

  1.    (3x-4)²- (x-3)²- 3(x-2)(2x-1)=0
    ⇔(3x-4-x+3)(3x-4+x-3)-3(2x²-5x+2)=0
    ⇔(2x-1)(4x-7)-6x²+15x-6=0
    ⇔8x²-18x+7-6x²+15x-6=0
    ⇔2x²-3x+1=0
    ⇔4x²-6x+2=0
    ⇔(2x-3/2)²-1/4=0
    ⇔(2x-3/2-1/2)(2x-3/2+1/2)=0
    ⇔(2x-2)(2x-1)=0
    ⇔\(\left[ \begin{array}{l}x=1\\x=1/2\end{array} \right.\) 

    Trả lời
  2. $(3x-4)^{2}$ $-$ $(x-3)^{2}$ $-$ $3$ $(x-2)$ $(2x-1)$ $=$ $0$
    ⇔ $(3x-4-x+3)$ . $(3x-4+x-3)$ $-$ $3$ $(x-2)$ $(2x-1)$ $=$ $0$
    ⇔ $(2x-1)$ . $(4x-7)$ $-$ $3$ $(x-2)$ $(2x-1)$ $=$ $0$
    ⇔ $(2x-1)$ . $[$ $4x$ $-$ $7$ $-$ $3$ $(x-2)$ $]$ $=$ $0$
    ⇔ $(2x-1)$ . $($ $4x$ $-$ $7$ $-$ $3x$ $+$ $6$ $)$ $=$ $0$
    ⇔ $(2x-1)$ . $($ $x$ $-$ $1$ $)$ $=$ $0$
    ⇔ $\left[\begin{matrix} 2x-1=0\\ x-1=0\end{matrix}\right.$
    ⇔ $\left[\begin{matrix} 2x=1\\ x=1\end{matrix}\right.$
    ⇔ $\left[\begin{matrix} x=\frac{1}{2}\\ x=1\end{matrix}\right.$
    Vậy $x$ ∈  $\frac{1}{2}$ ; $1$ 
    #chucbenhoctot:>>> 

    Trả lời

Viết một bình luận

Câu hỏi mới